Divine Names as the Standard of Ethics: A Translation of Ibn al-‘Arabī’s Concise Explanation of al-Asmā’ al-Ḥusnā - Badron, Mohd Sani (Afkar: Jurnal Akidah dan Pemikiran Islam, 2023)
The article submits that one of the most interesting notions in Islām is that the Names and Attributes of Allāh, also function as the standard of ethical manners and praiseworthy deeds. In order to clarify this notion—wherein there is an inevitable continuity of theology, worship and ethics—this article presents a translation of Ibn al-ʿArabī’s (560/1165—638/1240) concise explanation of the Divine Names (al-asmāʾul-ḥusnā). Given the fact that by his own claim, Ibn al-ʿArabī is ‘the seal of Muḥammadan sainthood’ (Khātim al-Awliyāʾ al-Muḥammadiyyah), and by his followers’ estimation ‘the supreme preceptor’ (al-Shaykh al-Akbar), the annotated translation’s contribution to present-day knowledge includes his notion of the oneness of the Divinity, list of some of the Divine Names, and understanding of their realities and meanings. At that ontological plane of the Divine Oneness, the Essence describes Himself according to His Beautiful Names and Sublime Attributes, all of which require recognition and acknowledgement by His servants for their own well-being in relation to takhallaqū bi-akhlāqillāh.